If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x + 3 = -1x Reorder the terms: 3 + 0.5x = -1x Solving 3 + 0.5x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 0.5x + x = -1x + x Combine like terms: 0.5x + x = 1.5x 3 + 1.5x = -1x + x Combine like terms: -1x + x = 0 3 + 1.5x = 0 Add '-3' to each side of the equation. 3 + -3 + 1.5x = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 1.5x = 0 + -3 1.5x = 0 + -3 Combine like terms: 0 + -3 = -3 1.5x = -3 Divide each side by '1.5'. x = -2 Simplifying x = -2
| 3(x+6)+103=8x-5(x-5) | | -13d-21=3(d+7)-10 | | 13x+5(x+1)=18(x+1)-13 | | 3-9x=5x-4 | | 4x+x+1=6 | | 3x^2-(2k-3)x-2k=0 | | 5.68-4.61x-1.9x=23.908 | | 7+9+b=40 | | -7x=-26+6x | | 2b-60=20 | | 2y^2-11y+14= | | x(-9+x)=0 | | 3x-1=-16 | | 6k=84 | | 11x-3=4-4x | | 5(x+6)=20 | | 28=-54 | | 18x-30=12x | | 63x^2-4x-35=0 | | 18-(3y-2)=2(y+2)+3y | | 3(3n-4)=4(2n-15) | | 3n-16=8n+29 | | X^2-16x+48=0 | | 4(4)(4*-2+2)= | | 4(4)(4x-2+2)= | | 9-3(5t-9)=-24 | | d^4=16d^2-48 | | 1.5s-.15=.6s+.0075 | | 4x-(xy+2)= | | 5x-4x+2=5 | | x^2+19x-10=0 | | 6x^2+19x-10=0 |